2003
DOI: 10.1029/2002jd002755
|View full text |Cite
|
Sign up to set email alerts
|

Ozone absorption around 10 μm

Abstract: [1] A careful comparison of four sets of ozone line intensities measured independently in the 10 mm region has been achieved. It is demonstrated that three of the experimental sets agree to better than 2% whereas the last one is consistently 4.4% higher. This is also the case for the ozone line intensities given in the HITRAN database, which are about 4% higher than the values given in the three experimental sets in agreement. New and more accurate transition moment constants for the n 1 and n 3 bands of 16 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 10 publications
1
38
1
Order By: Relevance
“…The transition moment parameters of Ref. [128] for {(101),(030)}-(010) bands and those extrapolated from cold bands [141] were used. (213), (321) and (114) upper states.…”
Section: -1541 CM −1 : Hot Bands Towards the Tetrad Regionmentioning
confidence: 99%
“…The transition moment parameters of Ref. [128] for {(101),(030)}-(010) bands and those extrapolated from cold bands [141] were used. (213), (321) and (114) upper states.…”
Section: -1541 CM −1 : Hot Bands Towards the Tetrad Regionmentioning
confidence: 99%
“…The first version "mipas pf2.0" was based on both the 1996 version of HITRAN and on new laboratory spectroscopic data and new calculations (Flaud et al, 2003a;Flaud et al, 2003b). After launch, version "mipas pf3.1" of the MIPAS dedicated spectroscopic database was released.…”
Section: Spectroscopic Database For Mipas Retrievalsmentioning
confidence: 99%
“…The atmospheric comparison of Kagawa et al (2007) between concentrations from TOMS (UV) and from ground-based FTS (IR) does not directly depend on the intensities in the ν 1 fundamental. But the fact that most atmospherically relevant ozone vibrational intensities in HITRAN directly depend on transition moments of the ν 1 and ν 3 fundamentals implies that IR intensities in the 3 µm region should be corrected by the same amount (Rothman et al, 2005;Flaud et al, 2003), implying that the discrepancy observed in their study is resolved at the same time.…”
Section: Atmospheric Implicationsmentioning
confidence: 58%